Engineered Vascularized Flaps, Composed of Polymeric Soft Tissue and Live Bone, Repair Complex Tibial Defects. (18th February 2021) - Redenski, Idan; Guo, Shaowei; Machour, Majd; Szklanny, Ariel; Landau, Shira; Kaplan, Ben; Lock, Roberta I.; Gabet, Yankel; Egozi, Dana; Vunjak‐Novakovic, Gordana; Levenberg, Shulamit
Abstract: Functional regeneration of complex large‐scaled defects requires both soft‐ and hard‐tissue grafts. Moreover, bone constructs within these grafts require an extensive vascular supply for survival and metabolism during the engraftment. Soft‐tissue pedicles are often used to vascularize bony constructs. However, extensive autologous tissue‐harvest required for the fabrication of these grafts remains a major procedural drawback. In the current work, a composite flap is fabricated using synthetic soft‐tissue matrices and decellularized bone, combined in vivo to form de novo composite tissue with its own vascular supply. Pre‐vascularization of the soft‐tissue matrix using dental pulp stem cells (DPSCs) and human adipose microvascular endothelial cells (HAMECs) enhances vascular development within decellularized bones. In addition, osteogenic induction of bone constructs engineered using adipose derived mesenchymal stromal cells positively affects micro‐capillary organization within the mineralized component of the neo‐tissue. Eventually, these neo‐tissues used as axial reconstructive flaps support long‐term bone defect repair, as well as muscle defect bridging. The composite flaps described here may help eliminate invasive autologous tissue‐harvest for patients in need of viable grafts for transplantation. Abstract : Large tissue defects necessitate autologous tissue harvest, perfused by a potent vascular network. In the current work, a composite neo‐tissue flap is fabricated from pre‐vascularized polymeric matrices and decellularized bones. By using high resolution in vivo imaging, the composite flaps are shown to support long‐term bone repair and vascularization, as well as soft‐tissue coverage.